Prevalence of prescribing topical corticosteroids to patients with lichen sclerosus following surgery for vulvar cancer: a survey among gynaecologic oncologists in The Netherlands - Féline O. Voss; Karelina L. Groenewegen; Hester Vermaat; Maaike C.G. Bleeker; Marc van Beurden (Journal of Obstetrics and Gynaecology, 2024)
Background Vulvar lichen sclerosus (LS) is a chronic inflammatory dermatosis which can progress to precursor lesion differentiated vulvar intraepithelial neoplasia (dVIN) and vulvar squamous cell carcinoma (VSCC). The risk of developing recurrent vulvar cancer following LS-associated VSCC is high. Evidence suggests that treatment of LS with topical corticosteroids (TCS) can prevent progression to dVIN, VSCC and recurrences. However, current guidelines do not give any recommendation on the management of LS following surgery for VSCC. The aim of this study was to conduct a survey among all registered gynaecologic oncologists (GOs) in the Netherlands to evaluate the current management of LS patients without a history of VSCC (LSnoVSCC) and patients with LS following surgery for VSCC (LSVSCC).Methods An online survey was distributed to all registered GOs in the Netherlands. Primary outcome measures were the frequency, type and duration of TCS treatment prescribed for LSnoVSCC and LSVSCC patients, separately. As a secondary outcome measure, reasons for treating or not treating patients with LSnoVSCC and LSVSCC with TCS were analysed.Results Forty-four GOs completed the survey, resulting in a response rate of 75%. TCS were prescribed more often to patients with LSnoVSCC as compared to patients with LSVSCC (86% versus 52%, respectively, p < 0.001). If treatment was initiated, ultra-potent (class IV) TCS were most commonly prescribed for an indefinite period of time for both patient groups. The most reported reason for treating patients in both groups with TCS was symptoms, followed by clinical aspects of the lesion and prevention of progression to dVIN and VSCC.Conclusion The majority of GOs who participated in our study endorse the utilisation of long-term ultra-potent TCS therapy in both patients with LSnoVSCC and LSVSCC. Nevertheless, Dutch GOs are currently prescribing TCS more frequently to patients with LSnoVSCC than to patients with LSVSCC.